The Comanche empire - Hämäläinen, Pekka, 1967- (Lamar series in western history., 2008)
Discusses the power wielded by the Comanches in the eighteenth and nineteenth centuries in the southern Great Plains, the Southwest, and northern Mexico, covering their military ability, political dominance, and commercial and cultural influence as they resisted European colonization until their defeat in 1875.